2018
DOI: 10.1108/jgm-10-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

High-skilled female immigrants: career strategies and experiences

Abstract: The motivation for this study is to uncover career-related issues that high-skilled female immigrants face and their strategies for rebuilding their careers upon migration to a new land.To explore this topic, we performed in-depth interviews with 14 Turkish female immigrants in the U.S. who have successfully rebuilt their careers from scratch upon migration. Content analysis of in-depth interviews with key informants on the subject revealed five theoretical themes that captured the career experiences of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 76 publications
(160 reference statements)
3
19
0
2
Order By: Relevance
“…Treuren, Manoharan and Vishnu (early view), however, have provided some evidence for the differences between skill-discounted migrants and other recently arrived migrants, across all industries and within the hospitality sector. Even less is understood about the different experiences of male and female migrants (Colakoglu et al., 2018; Guo and Al Ariss, 2015; Ressia et al., 2017b). Researchers have suggested that female migrants experience a double disadvantage, that of migrants and as women (Raijman and Semyonov, 1997).…”
mentioning
confidence: 99%
“…Treuren, Manoharan and Vishnu (early view), however, have provided some evidence for the differences between skill-discounted migrants and other recently arrived migrants, across all industries and within the hospitality sector. Even less is understood about the different experiences of male and female migrants (Colakoglu et al., 2018; Guo and Al Ariss, 2015; Ressia et al., 2017b). Researchers have suggested that female migrants experience a double disadvantage, that of migrants and as women (Raijman and Semyonov, 1997).…”
mentioning
confidence: 99%
“…The professional experiences and credentials of refugees are often unrecognized, challenged, and even discredited within host countries (Global Education Monitoring Report Team, 2018;Ratković, 2011Ratković, , 2013. Even when professional experiences and credentials are recognized, expectations for field-related work experiences within the host country serve as additional barriers to the attainment of meaningful employment (Colakoglu et al, 2018). Moreover, female immigrants are more likely to face unemployment or underemployment than male immigrants (Al Ariss, 2010;van den Bergh & Du Plessis, 2012).…”
Section: Reflections and Discussionmentioning
confidence: 99%
“…Several studies have found that the small reward for high-skilled migrants in remunerated employment explains why they choose self-employment to obtain higher income (Davidsson and Honig 2003;Constant and Zimmermann 2006). It also explains why only some migrants accept overqualified positions until they can save enough money to develop an entrepreneurial initiative (Paulson and Townsend 2004;Colakoglu et al 2018). Under this assumption, skilled migrants face auto-selection due to labour market conditions in the host country (e.g., work permits, recognition/ accreditation of diplomas, protective laws for locals, etc.…”
Section: Individual Characteristicsmentioning
confidence: 99%